SDG9 - industry, innovation and infrastructure - Velazquez, Luis, active 2021 (Concise guides to the United Nations Sustainable Development Goals., 2021)
As one of the few of the 17 SDGs applicable in industrial settings, SDG9 seeks to find new steps towards achieving sustainable industrialization. This book explores the fascinating and cross-cutting aspects that jeopardize achieving SDG9 - Industry, Innovation, and Infrastructure. Understanding that the UN's insistence on fostering sustainable industrialization has not rendered the expected results, and that the COVID-19 pandemic has exacerbated conditions in almost all sectors, Luis Velazquez explores the factors that have complicated the road towards achieving SDG9. Investigating the good practices around implementing SDG9, the author addresses fundamental concepts such as sustainability reporting, resilient infrastructure, sustainable connectivity, sustainable innovation, and more. Presenting information in a simple, clear and logical style, this book is must-have reading for undergraduate and postgraduate students, professors, and any supporter of SDG9 and Agenda 2030. Concise Guides to the United Nations Sustainable Development Goals comprises 17 short books, each examining one of the UN Sustainable Development Goals. The series provides an integrated assessment of the SDGs from economic, legal, social, environmental and cultural perspectives.